General Gorgas Buried; Nations Pay Honor, The Washington Post, Washington, D. C., August 17, 1920
This is an item from the William Crawford Gorgas Papers. This collection includes material created by and written about Gorgas, as well as material created by Gorgas' family members. His diaries and journals illuminate his life and work for the U.S. Army as a surgeon and span the years he worked in Cuba and Panama. The collection includes official reports and other documents Gorgas wrote and collected, as well as articles and other publications written about Gorgas and his work in sanitation and disease prevention, particularly yellow fever. Correspondence, articles, and other items document the numerous awards and tributes Gorgas received during his life and memorials after his death in 1920. In addition to William Crawford Gorgas material, the collection includes other material belonging to Gorgas family members including Marie Gorgas and their daughter, Aileen Gorgas Wrightson. In 1924, his widow Marie Gorgas published William Crawford Gorgas: His Life and Work. This collection includes manuscripts, galley proofs, and published versions of her work.Gift of Aileen Gorgas Wrightson, 1947 and 1952; Thomas W. Martin, 1952; Jessie Palfrey Leake, Minna Palfrey Tait, Aileen Gorgas Wrightson, Gene Palfrey Ellis, and William Gorgas Palfrey, 1958; Gorgas Memorial Institute of Tropical Medicine and Hygiene and National Library of Medicine, 1991; and Dr. William G. Palfrey and Gene Marie Palfrey Ellis, 1993The digitization of this collection was funded by a gift from EBSCO Industries.